Essentials of NEPSY assessment - Kemp, Sally L. (John Wiley & Sons, 2001)
An interpretive and administrative guide to NEPSY, a developmental neuropsychological test which is designed to be used by school psychologists, neuropsychologists, and research psychologists to assess children with developmental disabilities and to develop effective intervention strategies.